Manual for cocoa extension in Ghana - Ghana Cocoa Board (2018)
Manual Draft Copy: For sustainable production of cocoa it is the view of the Cocoa Health and Extension Division (CHED) of the COCOBOD to have highly trained and motivated human resource to facilitate the processes, which can lead to increased and sustained cocoa production. Though there are a lot of training materials available to train the Ghanaian small holder cocoa farmers, some of the information provided by such materials conflict with the recommendations based on scientific research findings. Such materials tend to confuse the farmer and end up undermining the trust reposed in the agents of extension delivery to farmers. This state of affair has plagued extension delivery for a considerable length of time. Most stakeholders in the cocoa industry have identified the constraint posed by the multiplicity of confusing messages delivered to farmers. The need for harmonising extension messages has become a priority activity for CHED and its partner organizations that have interest in facilitating increased productivity and sustainability of cocoa in Ghana. A common goal is to facilitate the production of an extension manual, illustrative guide and a step by step training guide with modules on basic cocoa extension to meet the rapid growth for knowledge and skills in the cocoa industry. There has been the need for a closer collaboration between CHED and major partners to engage national experts to produce a harmonized manual containing standard initiatives, messages and best practices for cocoa production and post production handling of high grade cocoa beans. It is hoped that this manual also helps to increase productivity of the cocoa sector, as certification is also covered in the manual to add premium to cocoa produced in Ghana. It is our view that only a productive cocoa farm will attract the younger farmer generation to carry on with cocoa production as a viable business option. This manual is intended for professional cocoa extension agents, field supervisors and trainers who have a degree or diploma in agriculture and are involved in training of other trainers and/or farmers. This extension manual can mainly be used by the master trainers, practitioners and extension officers with direct contact with cocoa farmers. If used by master trainers, this manual can also serve to train farmers directly. Special guidelines have been developed separately for Extension agents/facilitators and lead farmers to train farmers. The extension manual is supported by a training guide in modules, and an illustrative production guide for use by farmers. These materials help the trainer to structure the delivery of the training sessions to enhance achievement of the most impact of the training. It is the wish of COCOBOD in general and CHED in particular, that this collaboration with its partners,is to achieve the highest level of training for extension officers who are capable of facilitating farmer adoption of technologically advanced knowledge and skills to sustain the cocoa industry. It is our fervent hope that the developed materials will contribute to the removal of multiplicity of extension messages, which confuse the cocoa farmer. It is also our wish that the materials containing harmonized messages are used by stakeholders for cocoa extension in Ghana